Association between the ratio of serum eicosapentaenoic acid to arachidonic acid and risk of coronary artery disease in young Chinese patients - Liu, Xiong; Sun, Lichang; Wen, Weixing; Qiu, Min; Luo, Jianjing; Li, Weiwen; Hao, Shali; He, Mingli; Wu, Jiandi; Hu, Yunzhao; Huang, Yuli (Frontiers in Nutrition, 2022)
Objective: Long-chain (LC) omega-3 PUFAs, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may play an anti-inflammatory effect and decrease the risk of coronary artery disease (CAD). In contrast, omega-6 PUFA, mainly arachidonic acid (AA), has pro-inflammatory and pro-aggregatory effects, which may increase the risk of CAD. This study evaluated the associations between EPA, DHA, AA, and their ratios (EPA/AA and DHA/AA) with the risk of CAD in young Chinese patients. Methods: 182 young patients with CAD and 143 age-matched controls were included. Traditional cardiovascular risk factors were recorded. Serum EPA, DHA and AA were measured by ultra-performance liquid chromatography-mass spectrometry. Results: The level of AA was significantly higher, while the level of EPA was lower in the CAD group than that in the control group. There was no significant difference in DHA level in the two groups. Both the ratios of EPA/AA and DHA/AA were lower in the CAD group than that in the control. Multivariate logistic regression analysis showed that higher serum AA level was associated with the increased risk of CAD, while EPA was a protective factor for CAD. There was no significant association between DHA level and the risk of CAD. Although both higher ratios of EPA/AA (per tertile increment, adjusted odds ratios [OR] 0.356, 95% confidence intervals [CI] 0.247-0.513) and DHA/AA (adjusted OR=0.465, 95%CI=0.332-0.653) were associated with a lower risk of CAD in young patients. Receiver operating characteristic curve analysis showed that compared with AA, the diagnostic value was increased in EPA/AA, but not in DHA/AA. Conclusions: EPA, but not DHA may play a protective role in CAD, while AA may be associated with the increased risk of CAD in young Chinese patients. The ratio of EPA/AA can increase the predictive value for diagnosing CAD than EPA or AA alone.